Relationship Of Knowledge Level With Adherent Behavior Of Low-Salt Diet In Hypertensive Patients - Sari, Apriliya Norindah; Sumardino, Sumardino; Sunaryo, Tri; Sugiyarto, Sugiyarto; Rakhmawati, Dewi (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Hypertension presents a contribution to nearly 9.4 million deaths annually, attributed to cardiovascular disease. A low-salt diet is intended to help lower high blood pressure and to maintain blood pressure to remain normal. The purpose of this study is to knowing the level of knowledge relationship with obedient low-salt diet in hypertensive clients Giriwoyo work district. research design uses an analitic descriptive design by taking advantage of a sectional cross approach. There are significant connections between the level of knowledge of hypertension and the obedient diet of low salt clients of hypertension working district Giriwoyo.